Digital Marketing Strategy Analysis of Hidden Farm Café as a Hidden Gem in Bandung - Sandy Adithia; Raden Adi Cahyadi (Journal of Research on Business and Tourism, 2025)
Indonesia’s culinary industry has grown significantly, especially among ventures that adopt unique concepts to attract consumers. One emerging trend is the “hidden gem” approach, where remote locations are embraced as part of a brand’s charm. In Bandung, a city known for its creative energy, the Dago Pakar area offers a perfect setting for such businesses. Hidden Farm Café exemplifies this trend, combining a secluded location with organic homemade meals and a cozy atmosphere that appeals to the growing demand for “healing” experiences. The Café leverages social media, particularly TikTok and Instagram, to reach wider audiences and promote its unique appeal. It has successfully attracted communities such as cyclists and young urbanites seeking authentic culinary destinations. However, this study finds that Hidden Farm Café’s digital marketing remains underutilized due to inconsistent content and weak social media strategy, limiting its outreach and growth potential. Despite these challenges, Hidden Farm Café showcases how culinary businesses can thrive off the beaten path through strong brand identity and targeted digital promotion. With improved digital marketing execution, the hidden gem model can offer a sustainable path for creative culinary ventures in Bandung and beyond.